The Influence of Culture on the Implementation of Class X Physics Learning in State Senior High Schools in the City of Yogyakarta - Sri Wantoro; Suparwoto (Formosa Journal of Sustainable Research, 2022)
This study aims to determine the relationship of teacher culture to the implementation of research aspects of learning in class X physics at SMA Negeri Yogyakarta. The cultural aspects are learning culture and work culture. the research aspect is seen based on three stages namely planning, implementation, and reporting. This type of research is a qualitative descriptive research with a survey model. The research sample was a class X physics teacher at Yogyakarta City State Senior High Schools. Data collection techniques using a questionnaire / questionnaire. Data analysis with quantitative descriptive techniques. The results showed that the teacher's culture can affect the implementation of learning aspects of research in class X physics at SMA Negeri Yogyakarta. Teachers with very diligent cultural criteria have a greater percentage of implementation